Análisis del clima laboral en el proceso de Contratación Provincial de la Dirección Nacional de Gestión de Talento Humano en el Instituto Ecuatoriano de Seguridad Social, priorizando la comunicación interna, en el período septiembre 2016 – agosto 2017 : sistematización de la experiencia. - Vaca Baca, Jennifer Estefanía (2018)
Systematize the experience to unify the information that was collected and analyzed in the process of Provincial Contracting of the Ecuadorian Institute of Social Security (IESS), generating communication techniques whose applicability were practical and simple, the direct beneficiary was the Institution. The project was developed in the process of Provincial Contracting belonging to the National Direction of Management of Human Talent IESS, constituted by 8 servants with which the measurement of the Labor Climate was made; The evaluation was conducted from November 07, 2016 to May 05, 2017. The evaluation of the work climate periodically allowed us to know not only the aspects of interpersonal relationships that influenced productivity but also to establish the parameter under which we worked periodically. The projection of improvement of the working climate consented to optimize the process of Provincial Contracting, which will have a direct impact on the activities of the medical units of the Ecuadorian Institute of Social Security at the National level, since the incorporation of new officials was carried out with greater fluidity and effectiveness.